Statistical Sampling for Auditing and Accounting Decisions (Book). - Bruns, William J.; Vance, Lawrence L. (The Accounting Review, 1969)
Reviews the book, "Statistical Sampling for Auditing and Accounting Decisions: A Simulation," by Robert W. Vanesse.